Umbilical Cord Care Knowledge and Practice among Sample of Kurdish Women - Saadi, Hanaa Othman; Sdeeq, Hoger Sabbah; Hussein, Mhabad Muhammad; Blbas, Hazhar Talaat; Qadir, Kaify; Muhammed, Sima Muhsin (Technium BioChemMed, 2023)
Abstract: Background: The mother’s awareness and practices regarding cord care are crucial to the survival of the newborn. It’s because infections after birth most commonly enter through the cord stump. Practices for clean cord care aid in the prevention of infections, which lowers infant morbidity and mortality. Objective: The objective of this study was to investigate the knowledge and practices regarding newborn umbilical cord care among Kurdish mothers. Method: A descriptive study was carried out on 202 mothers at mala Fandi primary healthcare centre during middle year of 2023. data were collected through face-to-face questionnaire interviews. It consists of socio-demographic characteristics, the knowledge, and practices about cord care. Data were analysed by using Statistical Package for Social Sciences software version 23.0. Both descriptive and inferential analyses were done. Results: Out of 202 mothers (70.2%) of the mothers have a good knowledge about cord care and majority of the mothers (89.1%) have cleaned the umbilical cord stump of the baby and (40.6%) using the techniques named clean cord base and surrounding skin at the same time. Most of the mothers do not use any traditional substance (79.2%) while most of the learned about umbilical cord care by their parents (50%). age, Occupation, Level of education, type of family and residential area were influential factors with knowledge regarding cord care. Conclusion: most of mothers had good knowledge and proper practice about cord care. Also, majority of mothers got information from parents and relatives.